2 - Weakened States and Market Giants: Neoliberalism and Democracy in Niger and West Bengal - Idrissa, Rahmane (Africa Development, 2018)
This article argues that the contemporaneous phenomana of the ‘third wave of democratisations’ and the ‘second wave of liberalisations’ – or neoliberalism as it were – has disrupted the promise of democracy in the Global South. While the mainstream literature considers that democracy and the promotion of open market economies are mutually reinforcing, I claim that they in fact clash around the roles of the state, which both democracy and neoliberalism seek to reform, but in opposite directions. Democracy requires a broadened and responsive state system, mediating between social classes, while neoliberal reform typically shrinks the state system and shapes it to the preferences of elite classes. In this article, this thesis is explored in historical and comparative ways. I build an analytical framework through a comparison between the Bolivian National Revolution of 1952 and the democratic reforms undertaken under Evo Morales. Using this tool, I compare the fraught relations of Niger with French nuclear giant Areva and those of West Bengal with Indian industrial giant Tata. These comparisons, developed following descriptions of historical backgrounds, show why the vexed issue of the reform of the state should constitute a central research agenda if we are to grasp the fundamental conditions of the prospects of democracy in the Global South today.